Analisis Metode dan Bidang Pengembangan Sistem Informasi Menggunakan Systematic Literature Review - Maharani, Nindya Filza; Aldiansyah, Muhammad; Nugraha, Muhammad Aldo; Pibriana, Desi (Jurnal Teknologi Sistem Informasi, 2024)
The development of information systems is a crucial process in the current modern era, as information systems play a vital role in managing, processing, storing, retrieving data, as well as assisting in the necessary decision-making for organizational. Therefore, companies and organizations are competing to build information systems in the present era. However, the rapid growth of information technology results in new needs and challenges, prompting organizations to develop their information systems. A review was conducted to provide an understanding of why organizations in case studies need to develop information systems, the methods used, and the fields covered in the developed information systems. The review was conducted using the Systematic Literature Review (SLR) method, aiming to provide an overview of 14 papers discussing information system development from 2021 to 2023. The results indicate that the primary reason for an organization to develop an information system is the need for a system that can help manage employees more efficiently. Furthermore, the study found other reasons, such as assisting in the process of admitting new students, improving patient services, facilitating the book borrowing process, and managing student learning outcomes or E-Reports. The most widely used method for information system development is the Waterfall method, where information system development is widely implemented in the fields of education, business, healthcare, government, and human resources.